Implementation of Latest Technology in Oil and Gas Industry Business Processes: Case Study of Production Processes in Upstream Oil and Gas with Zero Flaring Technology - Muhammad Ardani; Tri Widjaja (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to evaluate and implement the latest technology in reducing flare gas (Flare Gas Recovery) in the upstream oil and gas industry. Flare gases, which are often burned and released into the atmosphere, are a significant source of emissions and a contributor to warming. The results of the SWOT and AHP analysis show that the technology of converting flare gas into electrical energy has advantages compared to other technologies. From an economic perspective, calculations show that this project is very feasible to implement, with an NPV value of IDR 48.82 billion, an IRR of 23.03%, a BCR of 1.14, and a payback period of only 4.27 years. The LCC of IDR 400.37 billion and the CoE of IDR 285.98/kWh indicate that this project can keep energy production costs at a competitive and sustainable level. This study concludes that Flare Gas Recovery to Electricity technology is the optimal solution to support zero flaring initiatives and make a real contribution to reducing flare gas emissions, as well as providing high added value in terms of economy and environment.